Study on Crop Planting Strategies in the Context of Sustainable Agricultural Development - Fan, Zhilin; Wang, Jiadong (Transactions on Environment, Energy and Earth Sciences, 2024)
In recent years, agricultural production has been showing a new trend of structural optimization and quality improvement with the economic growth. However, crop rotation involves a complex soil-crop-environment system, and different agricultural conditions and planting habits vary from region to region. Therefore, it is a challenge for farmers and management departments to formulate a reasonable crop rotation plan. For the problem of planting strategies, this study established a single-objective optimization model with the maximum stable profit, which solved the optimal planting scheme for the next 7 years of crops under the conditions of unsold waste and discounted sales. It also established a stochastic dynamic optimization model with the maximum uncertain profit, which solved the planting strategy problem under uncertain conditions. It has significant practical significance. The total profits for the next seven years under the scenario of unsold inventory waste and discounted sales are estimated at 11.37 million yuan and 23.77 million yuan.